Analisis Strategi dalam Mengatasi Kesulitan Pemecahan Pembagian Bersusun pada Soal Cerita Matematika di Sekolah Dasar - Fauziyah Kamilah Manar; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study explores strategies to address students' difficulties in understanding and solving mathematical word problems involving long division in elementary schools. These difficulties can stem from internal factors, such as a lack of conceptual understanding, low motivation, and inaccuracy in solving problems, as well as external factors, such as ineffective teaching methods and minimal use of instructional media. Using the Systematic Literature Review (SLR) method, this research examines previous studies that discuss the causes of learning difficulties and possible solutions. The findings indicate that a contextual approach based on Realistic Mathematics Education (RME) and the use of concrete teaching aids can significantly enhance students' comprehension of long division. This approach helps students connect learning with real-life experiences and visualize mathematical concepts more clearly. Therefore, innovative instructional strategies are essential to improve elementary school students' understanding and numerical skills.